Immediate effect of fluvastatin on lipid levels in acute coronary syndrome - Ostadal, Petr; Alan, David; Vejvoda, Jiri; Cepova, Jana; Kukacka, Jiri; Blasko, Peter; Martinkovicova, Lucia; Vojacek, Jan (Molecular and cellular biochemistry, 2007)
It is widely assumed that acute benefit of statin therapy is mediated especially by non-lipid effects. The immediate influence of statins on lipid levels in patients with acute coronary syndrome (ACS) is, however, not clear. A total of 64 consecutive patients with ACS were randomized at admission to fluvastatin 80 mg (Group 1, N = 32) or standard therapy without statin (Group 2, N = 32). The levels of total cholesterol (TC), low-density-lipoprotein cholesterol (LDL-C), high-density-lipoprotein cholesterol (HDL-C), and triglycerides (TG) were examined at admission and after 24 h. Baseline characteristics were comparable in both groups. In Group 1, fluvastatin significantly decreased the levels of TC by 14.5%, LDL-C by 17.2%, and HDL-C by 10.0% (P < 0.001); TG were not influenced. In Group 2 only marginal reductions in TC (by 4.1%, P = 0.03) and HDL-C (by 7.5%, P < 0.01) were detected; the levels of LDL-C and TG were not changed. As compared with Group 2, in Group 1 the final levels of TC (P = 0.02) and LDL-C (P = 0.01) were significantly lower. Fluvastatin therapy, when started at admission in patients with ACS, significantly reduces TC and LDL-C already after 24 h. We suggest that the lipid-lowering effect of statins in the therapy of ACS is probably as prompt as non-lipid effects.
Keywords: Cholesterol; statiny; indoly; Triglycerides; Cholesterol, HDL; Cholesterol, LDL; Humans; kyseliny mastné mononenasycené; Indoles; cholesterol; lidé středního věku; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Female; fluvastatin; Fluvastatin; výsledek terapie; lidé; Antioxidants; LDL-cholesterol; Acute Coronary Syndrome; antioxidancia; triglyceridy; ženské pohlaví; Male; Middle Aged; Treatment Outcome; HDL-cholesterol; akutní koronární syndrom; mužské pohlaví; Fatty Acids, Monounsaturated